1998
DOI: 10.1063/1.122922
|View full text |Cite
|
Sign up to set email alerts
|

Activation studies of low-dose Si implants in gallium nitride

Abstract: The implantation of Si ions into undoped high-resistivity GaN films is of interest for the realization of high-performance digital and monolithic microwave integrated circuits. We report the effect of postimplant annealing conditions on the electrical, optical, and surface morphology of Si ion-implanted GaN films. We demonstrate high activation efficiencies for low-dose Si implants into unintentionally doped GaN/sapphire heteroepitaxial films. The Si ions were implanted through an epitaxial AlN cap layer at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…As for ion-implantation doping of GaN, several n-and p-type implantation techniques have already been reported with the use of Si 6,8,9,[13][14][15][16][17][18][19][20] being the most common dopant for n-type, and Be 21-24 and Mg 8,9,13,22,25 the main elements implanted for p-type doping. The combination of n-and p-type implantation-doping techniques is expected to be a powerful tool for fabricating smart electronic devices such as a power switch.…”
Section: N-type Doping Characteristics Of O-implanted Ganmentioning
confidence: 99%
“…As for ion-implantation doping of GaN, several n-and p-type implantation techniques have already been reported with the use of Si 6,8,9,[13][14][15][16][17][18][19][20] being the most common dopant for n-type, and Be 21-24 and Mg 8,9,13,22,25 the main elements implanted for p-type doping. The combination of n-and p-type implantation-doping techniques is expected to be a powerful tool for fabricating smart electronic devices such as a power switch.…”
Section: N-type Doping Characteristics Of O-implanted Ganmentioning
confidence: 99%
“…This is particularly true for GaN implanted with the acceptor or donor species at lower doses (Ͻ10 15 cm Ϫ2 ). Eiting et al 8 reported only 17% electrical activation efficiency for the GaN implanted with Si at a dose of 4 ϫ 10 14 cm Ϫ2 with 100 keV after annealing at 1150°C for 5 min. Molnar et al 4 implanted a total dose of 4.4 ϫ 10 14 cm Ϫ2 Si ions with multiple energies, annealed at 1150°C for 2 min, and obtained only 1% donor activation, assuming a donor ionization energy of 26 meV.…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports have shown that Si ϩ implants can be efficiently activated in n-type GaN by N 2 -ambient annealing at temperatures у1000°C. [5][6][7][8] In this study, n ϩ -GaN films were formed by multiple 28 Si ϩ implantation into p-type GaN. After implantation, samples were thermal annealed in N 2 ambient.…”
Section: Introductionmentioning
confidence: 99%